2010
DOI: 10.1113/expphysiol.2010.055434
|View full text |Cite
|
Sign up to set email alerts
|

Role of sensory nerves in the rapid cutaneous vasodilator response to local heating in young and older endurance-trained and untrained men

Abstract: The ability to increase skin blood flow (SkBF) rapidly in response to local heating is diminished with advanced age; however, the mechanisms are unclear. The primary aim of this study was to investigate the role of sensory nerves in this age-related change. A secondary aim was to investigate the effect of aerobic fitness on sensory nerve-mediated vasodilatation in young and aged skin. We measured SkBF (using laser Doppler flowmetry) in young and older endurancetrained and untrained men (n = 7 in each group) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 30 publications
5
43
1
Order By: Relevance
“…4). The plateau phase differed significantly between the untreated control sites (86 ± 4%CVC max ) and the BT-treated sites (78 ± 3%CVC max ) during heating As previously shown, there was a reduced initial peak with EMLA during heating at 42 • C and no difference in the plateau phase (Minson et al 2001;Tew et al 2011a). During conditions of rapid local heating to 44 • C at both untreated and EMLA-treated sites there was no initial peak.…”
Section: Sympathetic Nerve Involvementmentioning
confidence: 70%
See 2 more Smart Citations
“…4). The plateau phase differed significantly between the untreated control sites (86 ± 4%CVC max ) and the BT-treated sites (78 ± 3%CVC max ) during heating As previously shown, there was a reduced initial peak with EMLA during heating at 42 • C and no difference in the plateau phase (Minson et al 2001;Tew et al 2011a). During conditions of rapid local heating to 44 • C at both untreated and EMLA-treated sites there was no initial peak.…”
Section: Sympathetic Nerve Involvementmentioning
confidence: 70%
“…The EMLA cream was applied to an area of 8 cm 2 under an occlusive dressing and left for a minimum of 2 h (Johnson et al 2005;Hodges et al 2007;Tew et al 2011a). The area was tested for sensory loss both before the study began and at its completion by pin-prick and pinching of the skin (Hodges et al 2007;Tew et al 2011a).…”
Section: Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was determined through a priori power analysis that seven participants would be required with an α of 0.05 and β of 0.90, with standard deviations and expected required mean differences established through our laboratory's previous work utilizing cutaneous sensory nerve blockage and local skin heating (Tew et al 2011a;Carter and Hodges 2011) (nQuery Advisor, v. 3).…”
Section: Participantsmentioning
confidence: 99%
“…The initial vasodilatory response, at least in the forearm, is thought to be primarily mediated by both sympathetic and sensory nerves (Minson et al 2001(Minson et al , 2002Tew et al 2011a;Carter and Hodges 2011), with transient receptor potential vanilloid (TRPV) type 1 ion channels (Wong and Fieger 2010) located on sensory afferent nerves. Additionally, these studies have reported that sensory nerves do not appear to be involved in the secondary sustained vasodilatation during prolonged local skin heating.…”
Section: Introductionmentioning
confidence: 99%